Carbon Dots as a New Class of Diamagnetic Chemical Exchange Saturation Transfer (diaCEST) MRI Contrast Agents. (24th June 2019) - Zhang, Jia; Yuan, Yue; Gao, Minling; Han, Zheng; Chu, Chengyan; Li, Yuguo; van Zijl, Peter C. M.; Ying, Mingyao; Bulte, Jeff W. M.; Liu, Guanshu
Abstract: While carbon dots (C‐dots) have been extensively investigated pertaining to their fluorescent, phosphorescent, electrochemiluminescent, optoelectronic, and catalytic features, their inherent chemical exchange saturation transfer magnetic resonance imaging (CEST MRI) properties are unknown. By virtue of their hydrophilicity and abundant exchangeable protons of hydroxyl, amine, and amide anchored on the surface, we report here that C‐dots can be adapted as effective diamagnetic CEST (diaCEST) MRI contrast agents. As a proof‐of‐concept demonstration, human glioma cells were labeled with liposomes with or without encapsulated C‐dots and implanted in mouse brain. In vivo CEST MRI was able to clearly differentiate labeled cells from non‐labeled cells. The present findings may encourage new applications of C‐dots for in vivo imaging in deep tissues, which is currently not possible using conventional fluorescent (near‐infrared) C‐dots. Abstract : Tief‐Punkte : Metallfreie Kohlenstoffpunkte (C‐dots) sind verwendbar als Magnetresonanztomographie(MRT)‐Agentien infolge des chemischen Austauschs oberflächenverankerter Protonen mit Wasser. Dank dieser inhärenten CEST‐Magnetresonanzeigenschaft lassen sich C‐dots in vivo in tief liegenden Geweben visualisieren. CEST: Sättigungstransfer durch chemischen Austausch.